2017
DOI: 10.3390/tropicalmed2030022
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against CNS-Targeted Rabies Virus Infection is Dependent upon Type-1 Immune Mechanisms Induced by Live-Attenuated Rabies Vaccines

Abstract: Rabies remains a major public health issue worldwide, especially in developing countries where access to medical care can represent a real challenge. While there is still no cure for rabies, it is a vaccine-preventable disease with pre- and post-exposure prophylaxis regimens approved by the World Health Organization (WHO). However, many rabies-exposed individuals have limited access to vaccines and virus-neutralizing antibodies approved for post-exposure prophylaxis. Unfortunately, any delay in the administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It is generally assumed that immunization with inactivated RABVs elicits a species independent type-2 response with high levels of type-2-associated IgG1 RABV-specific antibodies [ 28 , 29 ], while live attenuated RABV vaccines induce type-1 responses [ 36 , 62 ]. The results presented here as well as in previous studies support the predominance of type-1 immunity protection of live-attenuated RABVs and modified live vectored RABV vaccines in vaccinated mice [ 63 ] and carnivores, including foxes [ 36 , 37 , 48 ], since independent of the route of administration the immune response to SPBN GASGAS was mainly IgG2 driven ( Figure 3 ). This was also reflected by the significant correlation between total IgG and IgG2 levels, which are critical for protection against lethal rabies infection [ 64 , 65 ] with VNA and binding antibodies ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally assumed that immunization with inactivated RABVs elicits a species independent type-2 response with high levels of type-2-associated IgG1 RABV-specific antibodies [ 28 , 29 ], while live attenuated RABV vaccines induce type-1 responses [ 36 , 62 ]. The results presented here as well as in previous studies support the predominance of type-1 immunity protection of live-attenuated RABVs and modified live vectored RABV vaccines in vaccinated mice [ 63 ] and carnivores, including foxes [ 36 , 37 , 48 ], since independent of the route of administration the immune response to SPBN GASGAS was mainly IgG2 driven ( Figure 3 ). This was also reflected by the significant correlation between total IgG and IgG2 levels, which are critical for protection against lethal rabies infection [ 64 , 65 ] with VNA and binding antibodies ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that wild-type RABV is efficiently protected from clearance by an almost exclusive intraneuronal spread, the capacity to stimulate RABV-specific type-1 immunity mediating antibody-dependent cellular cytotoxicity (ADCC) or complement-dependent cytotoxicity (CDC) is an essential basis for an effective rabies vaccine [ 33 ]. Therefore, single immunization with live-attenuated vaccine confers superior, long-lasting protection against wild-type virus challenge compared to inactivated vaccines [ 36 ]. It seems that the anti-dog-IgG2 used in our study recognizes an IgG subclass that is thought to induce strong ADCC activity, whereas dog IgG1 does apparently not [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that MPLA could induce a strong Th1 response, which was associated with the induction of IgG2a and IgG2b antibodies in mice [20,21]. The Th1 response was associated with both the production of VNA and the clearance of wild type RABV from the central nervous system (CNS) [51]. The RABV-specific IgG isotyping test revealed that MPLA-supplemented inactivated rabies vaccines mainly induced Ig class switching to IgG2a and IgG2b, which implied a beneficial effect of adjuvant MPLA on the inactivated rabies vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The blood–brain barrier is a formidable concern when trying to deliver certain biologics to the CNS, especially in the treatment of encephalitis. To this end, data on further technological improvement for the use of a highly attenuated rabies virus recombinant vaccine in disease prevention and potential treatment is offered by Lebrun et al [ 23 ]. Needs for improved passive immunity via alternative methods to polyclonal immune globulins, such as monoclonal antibodies (MAb), were first described at the end of the 1970s.…”
mentioning
confidence: 99%